Rectoanal intussusception presenting as prolapsed anal mass - Izhar, NA; Sainal, Mohd. Yusof; Mohamad Salmi, Muhammad Irfan; Elagili, Faisal; Md Nor, Azmi (2023)
INTRODUCTION: Rectoanal intussusception is an invagination of the rectal wall into the lumen of the rectum. It is very rare to present as mass protruding from the anus. METHODS: We report a case of very rare presentation of adult rectoanal intussusception. CASE REPORT A 54 years-old healthy lady with presenting complain of mass protruding from the anus and per rectal bleeding for one day prior. Clinical examination revealed prolapsed anal mass with carpet like polyp and abundance of mucus discharge. There was no abdominal mass or tenderness. Mass was successfully reduced manually. Colonoscopy showed polypoidal growth at the rectum at 8cm from anus and biopsy was taken. we proceed with low anterior resection and intraoperatively noted rectoanal intussusception. Histopathological examination did showed tubullovilious adenoma with low grade dysplasia. Post-operative course complicated with anastomotic leak which required laparotomy, washout and drainage. She was then discharged well on post-operative day 13. CONCLUSION Rectoanal intussusception can present as prolapse through the anus in adults on rare occasions and should be investigated before definitive treatment. To preserve sphincter function, an initial reduction of colorectal intussusception should be attempted before surgery.